Meta Analisis Pengaruh Model Discovery Learning terhadap Literasi Sains Siswa - Laila, Rahmi (Universitas Negeri Padang, 2020)
The focus of this research study is a meta-analysis of the effect of Discovery Learnings Model on students' scientific literacy. This paper will reveal the importance of Discovery Learnings Model Â in the science and physics learning process in junior and senior high schools. The articles analyzed in this paper are articles obtained from various sources. The things learned start from the abstract, the contents and conclusions of the research. The method used is meta-analysis. The results of this study are a summary of the application of the Â Discovery Learning Model developed. The results showed the effect size of the Discovery Learning Model at the secondary school level was 1.00 while at the secondary level the effect size was 0.08. Then, in the subject matter indicator, the matter of global warming, temperature and heat, ecosystems, and dynamic fluid obtain successive effect sizes of 0.18; 0.12; 1.22; 1,00. then, in scientific literacy indicators, Effect Size in the scientific context i